Realization of the speech act of refusals among Malay ESL students - Saad, Norma (UUM Press, 2021)
Refusing to participate in an action is a negative response that might lead to a dispute and jeopardise the connection between the hearer and the speaker. To avoid the conflict that may arise when a speaker must decline a request, the speaker must offer an acceptable refusal and adjust to the position of the interlocutor as well as the circumstances of the situation. This study examined the strategies and sequence order of the strategies employed by Malay speakers of English as a second language (MSE) when they refused requests made by higher and equal status interlocutors. Twelve MSE undergraduates from a local university participated in the study. Data were collected using an open role-play which were transcribed, classified into semantic refusal strategies (Beebe et al., 1990) and categorized into the types of sequence orders of the strategies. The findings revealed that the MSE preferred indirect strategies when refusing higher and equal status interlocutors’ requests. When using direct strategies, they opted for lesser and the least degree of directness. The sequence orders of the strategies employed to refuse both interlocutors were also similar; immediate refusal and delayed refusal. However, they deferred in terms of their preference between the two types of sequence orders and the specific strategies used in the pre-refusal, head act and post-refusal. These variations show their effort to adapt to the status of their interlocutors; higher and equal status and the given situations. Their use of strategies at the post-refusal for both interlocutors were varied and lengthier compared to the sequence orders revealed in the previous studies. The findings reflect the participants’ effort to search for equilibrium between upholding their stance and at the same time remain respectful in the case of their employer and being concerned toward their friend. These findings provide pragmatic input which could be utilized by English language teachers to develop their students’ ability to use socially appropriate language for the situation they encounter in the Malaysian context.